Identification of ZNF26 as a Prognostic Biomarker in Colorectal Cancer by an Integrated Bioinformatic Analysis - Liu, Jiaxin; Li, Yimin; Gan, Yaqi; Xiao, Qing; Tian, Ruotong; Shu, Guang; Yin, Gang (Frontiers in Cell and Developmental Biology, 2021)
The dysregulation of transcriptional factors (TFs) leads to malignant growth and the development of colorectal cancer (CRC). Herein, we sought to identify the transcription factors relevant to the prognosis of colorectal cancer patients. We found 526 differentially expressed TFs using the TCGA database of colorectal cancer patients (n = 544) for differential analysis of TFs (n = 1665) with 210 up-regulated genes as well as 316 down-regulated genes. Subsequently, GO analysis and KEGG pathway analysis were performed for these differential genes for investigating their pathways and function. At the same time, we established a genetic risk scoring model for predicting overall survival (OS) by using the mRNA expression levels of these differentially regulated TFs and defined the CRC into low and high-risk categories which showed significant survival differences. The genetic risk scoring model included four high-risk genes (HSF4, HEYL, SIX2, and ZNF26) and two low-risk genes (ETS2 and SALL1), and validated OS in two GEO databases (p=0.0023 for the GSE17536, p=0.0193 for the GSE29623). To analyze the genetic and epigenetic changes of these six risk-related TFs, unified bioinformatics analysis was conducted. Among them, ZNF26 is progressive in CRC and its high expression is linked with poor diagnosis as well. Knockdown of ZNF26 inhibits the proliferative capacity of CRC cells. Moreover, the positive association between ZNF26 and cyclins (CDK2, CCNE2, CDK6, CHEK1) was also identified. Therefore, as a novel biomarker, ZNF26 may be a promising condidate in diagnosis and prognostic evaluation of colorectal cancer.